Pengelolaan Dana Pensiun Yang Efektif dan Efisien dalam Menjamin Kesejahteraan Keuangan di Masa Tua - Rusmini Icha Indryani; Lisna Nadila; Endah Wulandari; Amelia Septiani (Pusat Riset dan Inovasi Nasional, 2024)
QIncreasing life expectancy and the growth of the elderly population in Indonesia make pension fund programs an important solution in ensuring financial well-being in old age. This research aims to analyze important aspects in effective and efficient pension fund management to improve program performance and sustainability. The research method used is a qualitative approach with a case study design, through data analysis from journal articles and related news. The research results show that effective and efficient pension fund management is determined by several key factors, namely good governance and internal control, determining appropriate investment strategies, implementing a strong risk management system, compliance with regulations, adequate transparency and reporting, and strict supervision and audit. Apart from management factors, the success of a pension fund program is also influenced by individual participant factors, such as savings attitudes and future orientation. This research provides practical recommendations for pension fund managers to improve performance and ensure program sustainability, as well as educating the public about the importance of preparing for their financial future through pension fund programs.